Study of water vapour condensation using membranes - Ye, YuChu. (2013)
Use of liquid desiccant, specifically calcium chloride, for dehumidification of air had been investigated both in theory and experimentally. A membrane module with emphasis on membrane spacing and alignment was constructed for this project, together with an experiment rig that supports chemical dehumidification of air using liquid desiccant. Pre-experiment investigations were carried out to determine standards of desiccant concentration and range of system parameters for development of experiment procedures.